2017
DOI: 10.1016/j.cub.2017.01.047
|View full text |Cite
|
Sign up to set email alerts
|

RTN3 Is a Novel Cold-Induced Protein and Mediates Neuroprotective Effects of RBM3

Abstract: SummaryCooling and hypothermia are profoundly neuroprotective, mediated, at least in part, by the cold shock protein, RBM3. However, the neuroprotective effector proteins induced by RBM3 and the mechanisms by which mRNAs encoding cold shock proteins escape cooling-induced translational repression are unknown. Here, we show that cooling induces reprogramming of the translatome, including the upregulation of a new cold shock protein, RTN3, a reticulon protein implicated in synapse formation. We report that this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
85
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(94 citation statements)
references
References 49 publications
7
85
0
2
Order By: Relevance
“…However, mild hypothermia is an aggressive clinical therapy, bearing side‐effects such as shivering, slurred speech or mumbling, slow and shallow breathing, low energy and weak pulse . This inspired the search for molecular targets with fewer side‐effects to replace therapeutic cooling and led to the discovery of RBM3 as a crucial mediator of hypothermia‐related neuroprotection …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, mild hypothermia is an aggressive clinical therapy, bearing side‐effects such as shivering, slurred speech or mumbling, slow and shallow breathing, low energy and weak pulse . This inspired the search for molecular targets with fewer side‐effects to replace therapeutic cooling and led to the discovery of RBM3 as a crucial mediator of hypothermia‐related neuroprotection …”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence indicating that RBM3 is a crucial factor mediating hypothermia‐induced neuroprotective effects. In primary neurons and cortical organotypic slice cultures, mild hypothermia markedly increased RBM3 expression and rescued neuronal cells from forced apoptosis . In Alzheimer‐type and prion‐infected mouse models, RBM3 was identified as a crucial mediator of hypothermia‐induced neuroprotection, revealing that RBM3 induction/overexpression may provide protection not only in cases of acute brain injury but also in neurodegenerative diseases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that RBM3 is able to mitigate cell death due to neurodegenerative diseases 25,41. Interestingly, in that context, a recent study identified RTN3, a protein that is involved in synapse function, as a target of RBM3 42. Taken together, further research is needed to address the possible targets and molecular functions of RBM3.…”
Section: Discussionmentioning
confidence: 99%
“…A convenient alternative is the freeze-thawing method which entails successive freezing (−80 °C) of 2 ml layered sucrose solutions starting from the highest sucrose concentration (50%, 40%, 30%, 20%, 10% w/v sucrose solutions) (Bastide et al, 2017). …”
Section: Methodsmentioning
confidence: 99%